An integrative description of Pilatobius nuominensis sp. nov. (Tardigrada: Hypsibiidae) from China - Sun, Xue-Ling; Zhang, Jing-Yu; Wang, Ning; Zhao, Min; Luo, Xue-Gang (Zootaxa, 2021)
A newly identified tardigrade species from China, Pilatobius nuominensis sp. nov., belongs to the group of species with cuticle of the dorsal and lateral caudal region with evident irregular polygonal sculpture. Nucleotide sequences of two nuclear (18S rRNA, 28S rRNA) and one mitochondrial (COI) DNA fragments of the new species are provided, which allows an independent verification of the taxonomic status of the new species. This is the first record of the genus Pilatobius in the Great Hinggan Mountains.